Hubungan Sanitasi dengan Kejadian Diare di RS Pina Tambun Bekasi - Sari, Rani Wulan; Mulyanto, Tatag (Universitas Malahayati, 2025)
ABSTRACT Diarrhea is still the second leading cause of death after pneumonia. Diarrhea kills 5,25,000 children under five every year and can injure 1.7 million children worldwide. In America, there are 7-15 episodes of diarrhea experienced by each child aged 5 years on average, 9% of 5 year old children who suffer from diarrhea are hospitalized and 3000-5000 children die every year (Azis et al., 2021). The high prevalence of diarrhea in children can increase the incidence of stunting. The micro-substances used for children's growth and development will be used up to fight infection due to continuous diarrhea. The aim of the research is to determine the relationship between sanitation and the incidence of diarrhea at Pina Tambun Hospital, Bekasi in 2024. Research method. The population in this study was 60 respondents, so the method used in determining the sample for this study was an analytical survey using a cross-sectional research design using the chisquere test, processing data using a computer with the SPSS program application. Research results: From this research, there is a significant relationship with the incidence of diarrhea at Pina Tambun Bekasi Hospital in 2024, namely the variables of defecation behavior, CTPS behavior, waste processing and previous infections. From the research results it can be concluded that there is a significant relationship between defecation behavior and the incidence of diarrhea with 0.000 and CPTS behavior with p. value 0.001, waste management 0.000 and previous infection with a p value of 0.001, while for drinking water treatment there is no significant relationship with a p value of 0.105. Keywords: Incident of Diarrhea, Sanitation ABSTRAK Diare dapat membunuh 5.25.000 balita setiap tahun dan dapat melukai 1,7 juta anak di seluruh dunia. Di amerika, terdapat 7-15 episode diare yang dialami setiap anak yang berusia rata – rata 5 tahun, 9% anak 5 tahun yang terkena diare dirawat di rumah sakit dan 3000-5000 anak meninggal setiap tahunnya (Azis et al., 2021). Prevalensi diare yang tinggi pada anak dapat meningkatkan angka kejadian stunting. Zat mikro yang digunakan untuk pertumbuhan dan perkembangan anak akan habis untuk melawan infeksi akibat diare secara terus-menerus. Tujuan penelitian untuk mengetahui hubungan sanitasi dengan kejadian diare di RS pina tambun Bekasi tahun 2024. Metode penelitian Populasi dalam penelitian ini sebanyak 60 responden jadi metode yang digunakan dalam penentuan sampel penelitian ini adalah survey analitik dengan menggunakan rancangan penelitian cross-sectional menggunakan uji chisquere, pengelolahan data menggunakan computer dengan aplikasi program SPSS. Hasil penelitian Dari penelitian ini yang ada hubungan bermakna dengan kejadian diare di Rs pina tambun Bekasi tahun 2024 adalah variabel perilaku BAB, perilaku CTPS, pengolahan sampah dan infeksi sebelumnya. Dari hasil penelitian dapat di simpulkan bahwa ada hubungan yang bermakna antara perilaku BAB dengan kejadian diare dengan 0.000 dan perilaku CPTS dengan p. value 0.001, pengelolahan sampah 0,000 dan infeksi sebelumnya dengan p value 0,001 sedangkan untuk pengolahan air minum tidak ada hubungan bermakna dengan p value 0,105. Kata Kunci: Sanitasi, Kejadian Diare